Stability of shielded pentacenes under ambient conditions [data] - Ludwig, Philipp; Kilian, Paul; Mayerhofer, Patrick; Hippchen, Nikolai; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2024)
The stabilization of pentacene through variation of substituents serves as a test bed to access stable organic semiconductors, transferable to the larger soluble acenes and azaacenes. Pentacene is stable enough for derivatization via wet-chemistry but sufficiently labile to test its (induced) (photo)decomposition. In this article, we describe the synthesis of shielded pentacenes, either via covalent jacketing with ester macrocycles or via steric shielding with biphenylyl substituents, together with attempts to access a bis(ortho-quaterphenyl) substituted Geländer pentacene. The photostability of the pentacenes is assessed under ambient conditions (air, light) to simulate handling under typical laboratory conditions and put into perspective with reference compounds, such as TIPS-ethynylated, ether-jacketed or our previously reported Geländer pentacenes. (2024-11-28)
Gefördert durch: Deutsche Forschungsgemeinschaft (SFB): 1249; Deutsche Forschungsgemeinschaft: INST 40/575-1 FUGG; Deutsche Forschungsgemeinschaft: INST 35/1596-1 FUGG
Gesehen am 27.11.2024
Keywords: Forschungsdaten; Datenbank